The short- and long-term effects of school choice on student outcomes: Evidence from a school choice reform in Sweden - Verena Wondratschek; Karin Edmark; Markus Frölich (Research Institute of Industrial Economics (IFN), 2013)
This paper evaluates the effects of a major Swedish school choice reform. The reform in 1992 increased school choice and competition among public schools as well as through a large-scale introduction of private schools. We estimate the effects of school choice and competition, using precise geographical information on the locations of school buildings and children's homes for the entire Swedish population for several cohorts affected at different stages in their educational career. We can measure the long-term effects up to age 25. We find that increased school choice had very small, but positive, effects on marks at the end of compulsory schooling, but virtually zero effects on longer term outcomes such as university education, employment, criminal activity and health.
Keywords: I20; C21; 330; school choice; school competition; treatment evaluation; cognitive and non-cognitive skills